Fundamental Rights Review of National Measures: Nothing New under the Charter? - Jukka Snell (United Kingdom, 2022)
The case law under the Charter on the use of EU fundamental rights to scrutinize national measures represents a continuation of the earlier jurisprudence. The wording of Article 51(1) Charter of Fundamental Rights has not resulted in a general rollback of EU fundamental rights. However, the Charter has focused attention on the issue, has resulted in important new guidance and some streamlining of the case law, and will make it hard for the Court to push the jurisprudence further. The normative justification for the Wachauf type cases can be readily found and has been convincingly articulated by the Court. This does not mean that it will be easy to decide whether the connection between the EU rules and the national measure is sufficient to count as implementation, but the Court has helpfully distilled factors to be taken into account. By contrast, the normative justification for ERT type cases is more difficult to establish. This case law represents a far-going interference with national legal systems. The standard explanation, that since derogations are creatures of Union law, EU fundamental rights must apply, fails to convince. The Court is expressing its distrust of national systems of fundamental rights protection. Unfortunately the distrust may be warranted, and the political system of the EU may not be well equipped to correct matters. The case law can be defended as a judicial remedy for the failure of the political, but needs to be applied with care.